PREDIKSI PERUBAHAN TUTUPAN LAHAN MENGGUNAKAN CITRA SATELIT PENGINDERAAN JAUH PADA KAWASAN DESTINASI PARIWISATA SUPER PRIORITAS: STUDI KASUS KECAMATAN KOMODO, KABUPATEN MANGGARAI BARAT, NUSA TENGGARA TIMUR - Elisa Imania; Raka Ikmana (Badan Pusat Statistik Provinsi NTT, 2026)
Introduction: Labuan Bajo is designated as one of Indonesia’s five super priority tourism destinations. Background Problems: Population growth and rapid development of Labuan Bajo tourism destination have had a significant spatial impact on the Manggarai Barat Regency. Novelty: This study aims to analyze land cover changes in the Komodo District, Manggarai Barat Regency, during the period 2022-2024, predict land cover in 2027, and then analyze its relationship with sustainable tourism development. Research Methods: The data used in this study consists of land cover maps, road maps, and National Digital Elevation Model maps sourced from ESRI through Living Atlas and the Geospatial Information Agency. Land change potential modeling was conducted using Artificial Neural Network with Multi-Layer Perceptron structure. Findings/Results: The results of the land cover change modeling show that 90.76% of the land cover can be mapped correctly. The validity test results also indicate that the model performs very well with a Kappa value of 0.86009, making it suitable for predicting future land cover. The 2027 land cover prediction shows that compared to 2022, trees will decrease by 707.70 ha, while built-up area and rangeland will increase by 445.75 ha and 340.24 ha, respectively.